How Do Nascent Social Entrepreneurs Respond to Rewards? A Field Experiment on Motivations in a Grant Competition - Ina Ganguli; Chloé Le Coq; Marieke Huysentruyt (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2018)
We conducted a field experiment to identify the causal effects of extrinsic incentive cues on the sorting and performance of nascent social entrepreneurs. The experiment, carried out with one of the United Kingdom's largest support agencies for social entrepreneurs, encouraged 431 nascent social entrepreneurs to submit a full application for a grant competition that provides cash and in-kind mentorship support through a one-time mailing sent by the agency. The applicants were randomly assigned to one of three groups: one group received a standard mailing that emphasized the intrinsic incentives of the program, or the opportunity to do good (Social treatment), and the other two groups received a mailing that instead emphasized the extrinsic incentives - either the financial rewards (Cash treatment) or the in-kind rewards (Support treatment). Our results show that an emphasis on extrinsic incentives strongly affects who applies for the grant and consequently the type of submissions received. The extrinsic reward cues "crowded out" the more prosocial candidates, leading fewer candidates to apply and fewer applicants targeting disadvantaged groups. Importantly, while the full applications submitted by candidates in the extrinsic incentives groups were more successful in receiving the grant, their social enterprises were less likely to be successful at the end of the one-year grant period. Our results highlight the critical role of intrinsic motives to the selection and performance of social enterprises and suggest that using extrinsic incentives to promote the development of successful social enterprises may backfire in the longer run.
Keywords: C93; J24; L31; O35; 330; social entrepreneurship; field experiment; incentives; motivations; grants